The effect of aerobic exercise and omega-3 on the expression of telomeric repeat binding factor 1 and 2 and telomerase reverse transcriptase enzyme in the heart tissue of elderly HFD rats - Ghasem Torabi Palat Kaleh; Ahmad Abdi; Asieh Abbassi Daloii (Shahid Beheshti University, 2023)
Background and Purpose: Aging is a complex physiological process that involves progressive loss of body function and degradation of DNA strands located at the ends of chromosomes-telomeres. The capacity of cells to divide is determined by telomere length, as an excessive shortening of telomeres causes cellular senescence. Exercise training and omega-3 prevent the shortening of telomeres by affecting telomerase. The aim of the present study was to investigate the effect of aerobic training with omega-3 on some shelterins and telomerase of heart tissue in elderly high-fat diet rats. Materials and Methods: In this experimental study, 40 male Wistar rats (mean±SD weight, 311.3±26.95 g) were obtained from the Pasteur Institute and transferred to the laboratory. After transferring the rats to the laboratory, they were randomly divided into five groups: Normal Diet (ND), High-Fat Diet (HFD), High-Fat Diet-Training (HFDT), High-Fat Diet-Omega3 (HFDω3), and High-Fat Diet-Training-Omega3 (HFDTω3). HFD induction was performed using a high-fat diet containing 17% protein, 43% carbohydrate, and 40% fat. The supplement groups received 1 g of Omega3 (per kg of body weight) orally during the intervention period. The aerobic exercise training program at the beginning consisted of running on a treadmill at a speed of 10 m/min, 0-degree incline, for 15 minutes. The speed and duration gradually increased to 16 meters per minute and 50 minutes in the last session. Running was carried out for 8 weeks and five days a week. Data were analyzed by one-way analysis of variance and Tukey's post hoc test at the P<0.05. Results: Induction of HFD significantly decreased the expression of telomeric repeat binding factor 2 (TRF2) (P=0.002), telomerase reverse transcriptase enzyme (TERT) (P=0.024) and increased TRF1 (P=0.0001) compared to the ND group. Exercise and omega-3 significantly increased the expression of TRF2 and TERT in HFD rats (P<0.05). Moreover, TRF2 and TERT expression changes were higher in the HFDTω3 group compared to HFDT (P=0.023 and P=0.044, respectively) and HFDω3 groups (P=0.021 and P=0.042, respectively). Conclusion: The results of the present study showed that aging and HFD are associated with a decrease in TRF2, TERT and an increase in TRF1 in heart tissue, and aerobic exercise and omega-3 consumption can reverse this trend. Considering the role of shelterins and telomerase in cellular function, it seems that changing the levels of these indicators following physical activity and using omega-3 supplements can partially prevent the occurrence of many heart diseases caused by aging and obesity.